Who Is Happy? - Myers, David G.; Diener, Ed (Psychological Science, 1995)
A flood of new studies explores people's subjective well-being (SWB) Frequent positive affect, infrequent negative affect, and a global sense of satisfaction with life define high SWB These studies reveal that happiness and life satisfaction are similarly available to the young and the old, women and men, blacks and whites, the rich and the working-class Better clues to well-being come from knowing about a person's traits, close relationships, work experiences, culture, and religiosity We present the elements of an appraisal-based theory of happiness that recognizes the importance of adaptation, cultural world-view, and personal goals